2008
DOI: 10.1111/j.1365-2141.2008.07329.x
|View full text |Cite
|
Sign up to set email alerts
|

The subcellular Sox11 distribution pattern identifies subsets of mantle cell lymphoma: correlation to overall survival

Abstract: SummaryGene expression analysis demonstrated high expression of the neuronal transcription factor SOX11 in mantle cell lymphoma (MCL). In contrast to follicular lymphoma, small lymphocytic lymphoma and reactive lymphoid tissue, most MCLs tested (48/53 patients) expressed sox11 protein in the nucleus. Therefore nuclear sox11 expression represents a new tumour marker for a subset of MCL. However, 5/53 MCL cases expressed sox11 only in the cytoplasm; these MCL patients had a shorter survival compared to MCL with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
111
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(122 citation statements)
references
References 12 publications
9
111
1
Order By: Relevance
“…23 Wang and colleagues demonstrated shorter survival in 5/53 patients with SOX11 cytoplasmic protein expression compared to 48/53 with SOX11 nuclear protein expression. 24 Consistent with other reports that stated that 78-93% of cases are positive, we found that the great majority (91%) of nodal MCL cases express SOX11; however, in our cohort of indolent leukemic MCL cases only one of five showed low-level positivity. 9,11,21,25 This was statistically different from typical nodal MCL.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…23 Wang and colleagues demonstrated shorter survival in 5/53 patients with SOX11 cytoplasmic protein expression compared to 48/53 with SOX11 nuclear protein expression. 24 Consistent with other reports that stated that 78-93% of cases are positive, we found that the great majority (91%) of nodal MCL cases express SOX11; however, in our cohort of indolent leukemic MCL cases only one of five showed low-level positivity. 9,11,21,25 This was statistically different from typical nodal MCL.…”
Section: Discussionsupporting
confidence: 93%
“…7,9 The pattern has not been well characterized but appears to have no prognostic relevance. 24 Bone marrow findings have not been described in the type of patients with leukemic, non-nodal disease who are presented here. We show that there is uniformly low tumor burden in the marrow with sparsely distributed interstitial single cyclin D1 + lymphocytes or, uncommonly, subtle interstitial aggregates, representing less than 5% of cellularity.…”
Section: Discussionmentioning
confidence: 72%
“…These patients had shorter survival compared with mantle cell lymphomas with nuclear sox11 staining. 7 Ek et al evaluated sox11 expression in 18 whole tissue sections of mantle cell lymphomas, including 16 classical and 2 blastoid mantle cell lymphomas. One case was negative for nuclear sox11 staining, and this case was a blastoid variant.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Recently, sox11, a transcription factor involved in embryonic neurogenesis and tissue remodeling, has been found to be expressed in the nuclei of mantle cell lymphoma cells. 6,7 This intriguing finding raises the question about the possible association between the nuclear expression of sox11 and t(11;14)(q13;q32). 6 The SRY (sex-determining region Y)-box11 (SOX11) gene is mapped to chromosome 2p25 and belongs to the SRY-related high mobility group (HMG) box (SOX) gene family characterized by containing the HMG domain with high identity to the HMG domain in SRY.…”
mentioning
confidence: 98%
“…2 Common MCL simulators do not express nuclear SOX11 but questions remain as to its relation to cyclin D1 (CCND1) and whether SOX11 is restricted to MCL. We surveyed most categories of B-and T-cell lymphomas for SOX11, including plasmacytoma/myeloma 3 and hairy cell leukemia, which are characterized by elevated levels of CCND1.…”
Section: Introductionmentioning
confidence: 99%